2015
DOI: 10.1007/s00228-015-1958-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of non-steroidal anti-inflammatory drug/analgesic therapeutic duplication in the South Korean ambulatory care setting

Abstract: This study is the first to determine the prevalence of NSAID TD and the factors that were associated with its occurrence in South Korea. These results may help prevent TD and improve appropriate medication use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Moreover, duplicated prescriptions of NSAIDs may exacerbate NSAID‐associated adverse reactions (6). In a previous study, the prevalence of duplication of NSAIDs and analgesics was reported to be 13.3% of all prescriptions in Korea in 2011 (7), higher than the 8% in Iran (8) and the 5.4% in Belgium (9). The higher prevalence of therapeutic duplication (TD), defined as prescribing and dispensing 2 or more drugs in the identical therapeutic group, underlined the need for an appropriate risk management tool.
We assessed the effect of a nationwide real‐time drug utilization review (DUR) system on safe use of nonsteroidal antiinflammatory drugs (NSAIDs) among knee osteoarthritis patients, using a large administrative database. After implementing new DUR criteria on therapeutic duplication (TD) of NSAIDs, a significant decrease in the prevalence of NSAID TDs was observed, mainly involving TDs on separate prescriptions.
…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, duplicated prescriptions of NSAIDs may exacerbate NSAID‐associated adverse reactions (6). In a previous study, the prevalence of duplication of NSAIDs and analgesics was reported to be 13.3% of all prescriptions in Korea in 2011 (7), higher than the 8% in Iran (8) and the 5.4% in Belgium (9). The higher prevalence of therapeutic duplication (TD), defined as prescribing and dispensing 2 or more drugs in the identical therapeutic group, underlined the need for an appropriate risk management tool.
We assessed the effect of a nationwide real‐time drug utilization review (DUR) system on safe use of nonsteroidal antiinflammatory drugs (NSAIDs) among knee osteoarthritis patients, using a large administrative database. After implementing new DUR criteria on therapeutic duplication (TD) of NSAIDs, a significant decrease in the prevalence of NSAID TDs was observed, mainly involving TDs on separate prescriptions.
…”
Section: Introductionmentioning
confidence: 97%
“…NSAID duplication was previously investigated in Korea due to concerns of high rates of NSAID duplication. 26 , 27 In 21 million patient visits by individuals of all ages, Kang and colleagues 26 identified 59,636,222 NSAID prescriptions with 13.3% involving therapeutic duplication over the first 3 months of 2011. Follow-up study in Korea by Jung and colleagues 27 showed NSAID duplication fell to 5.6% after implementation of a nationwide drug utilization monitoring program.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we distinguished ED from duplication by ruling out accidentally overlapped prescriptions. By excluding those with less than 10% duplication during the total prescription period from the ED group, we tried to provide a more clinically significant definition of duplication of tramadol use than previous studies which defined one day or more of overlapping as duplication . Also, we identified factors that could affect tramadol use, including patients’ age and special comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature on duplicated tramadol use is sparse, one study found that the 1-year incidence rate of tramadol shopping behaviour was 1.0% (95% CI 0.7-1.5) in France. 16 Another study showed that the therapeutic duplication rate of NSAID/analgesic prescriptions in Korea was 13.3%, 25 and a third study found that 2.7% of Z-drug users in Ireland received duplicate prescriptions. 26 Tramadol is used frequently as an alternative to NSAIDs because it has fewer side effects on the kidney or stomach, which explains its wide usage in older adults or patients with a comorbid disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation